The views of teachers in England on an action-oriented climate change curriculum. Issue 11 (2nd November 2021) - Howard-Jones, Paul; Sands, David; Dillon, Justin; Fenton-Jones, Finnian
Abstract: To inform current debate around climate change education (CCE) in the school curriculum in England, we surveyed the views of primary and secondary teachers ( N  = 626). In England, direct reference to climate change in the National Curriculum is confined to secondary Science and Geography but, unrelated to their subject area, teachers favoured a cross-curricular approach with most already communicating to their students about it. Feeling comfortable delivering CCE was correlated with reported resource availability, with most teachers considering only basic literacy was a greater funding priority. Teachers supported an action-based CCE curriculum including issues of global social justice, beginning in primary school with mitigation projects such as conservation, local tree-planting and family advocacy. Local campaigning (e.g. legal demonstration) was considered appropriate around the primary/secondary transition, with most supporting inclusion of civil disobedience but indicating this should begin at secondary school (11+ years). Results are compared with a 2018 poll of US teachers.